Peran LPM Dinamika Sebagai Wadah Pemberitaan Mahasiswa Di Lingkungan Kampus UIN Sumatera Utara - Afriana Alawiah. AR; Jordan Yogaswara; Aisyah Nursashi Putriani; Riska Nurasnida Siregar; Khayrani Ramadani (CV. ITTC INDONESIA, 2026)
The Student Press Institute (LPM) Dinamika of UIN North Sumatra plays a vital role as a channel for aspirations and information distribution within the campus environment. This study aims to analyze the role of LPM Dinamika as a news outlet, the effectiveness of its information distribution strategies, and student perceptions of its reporting independence. The research method used is descriptive qualitative with a content analysis approach on the @lpmdinamika Instagram account for the period of November 2025–January 2026, as well as in-depth interviews with students. The results show that LPM Dinamika functions effectively as the campus's main information pillar, with hard news content (such as flood reports) receiving higher attention (10,873 views) compared to advocacy content. The information distribution strategy proved effective through the synergy of social media and the